(untitled) (Tribhuvan University Journal of Microbiology, 2021)
Objectives: This study aimed to determine the seroprevalence of brucellosis among pigs of commercial farms in Chitwan district of Nepal. Methods: This cross sectional prospective study was conducted among 100 pigs of commercial farms located in western region of Chitwan district of Nepal. Blood sample was collected from each pig by the trained veterinarians and serum was extracted. Each serum sample was processed for Rose Bengal plate test (RBPT) and ELISA for the detection of Brucella spp. Data was analyzed using SPSS software version 21.0 and a p-value of less than 0.05 was considered as significant. Results: Prevalence of brucellosis in pigs was found to be 15% (15/100) by RBPT and 10% (10/100) by ELISA. There was statistically insignificant difference (p=0.98) in gender wise prevalence of brucellosis among pigs. Younger pigs below one year of age were more susceptible to brucellosis than the older pigs. Landrace breed showed more positive test results compared to other breeds. Conclusion: Pigs can be the potential source of transmission of brucellosis to humans. Considering the high economic loss on livestock sector and possible transmission to humans, awareness program and appropriate control strategies is warranted. Breed and age factors should be considered while adopting the control measures of brucellosis among pigs.